Dialek Hokkaido sebagai Bentuk Alih Kode dan Campur Kode dalam Novel Poppoya - Zane, Sonny Rama Al Faridzi; Andini, Rizki (Japanology: The Journal of Japanese Studies, 2023)
This study analyzes code-switching and code-mixing in Jirō Asada's novel Poppoya, focusing on the Hokkaido dialect. A qualitative descriptive method was employed, utilizing both oral and written data extracted from the novel. Data collection involved thorough reading of the novel, noting sentences containing the Hokkaido dialect, translating these sentences, and categorizing conversations into code-switching and code-mixing groups. The analysis identified two main types of code-switching: internal code-switching and code-mixing, with variations in situational and metaphorical contexts. Code-mixing included original Japanese language elements in 37 instances. Causes of internal code-switching comprised changes in speaker, interlocutor, situation, and conversation topic, while code-mixing was influenced by role identification, mother tongue equivalence, and speaker habits. Examples of code-switching included transitioning to standard Japanese for a relaxed atmosphere, while code-mixing highlighted regional identity through the use of the Hokkaido dialect. The analysis underscores the impact of situational changes, social identity, and speaker habits on code-switching and code-mixing, reflecting the complexity of language in Japan's multicultural society.